Feeding strategies and intraspecific competition in German yellowjacket (Vespula germanica). - Michelina Pusceddu; Alessandra Mura; Ignazio Floris; Alberto Satta (PLoS ONE, 2018)
The German yellowjacket (Vespula germanica) is an opportunist predator and a scavenger, whose eclectic diet also includes honey, brood, dead and live honey-bees. There is no evidence in this species of coordinated attacks against bees involving other conspecifics, although intraspecific competition has been already reported between two or more individuals during feeding. Our aim was to gain further knowledge on the feeding behavior of V. germanica in order to evaluate its role in an apiary. Sight observations of predation and necrophagy behaviors were carried out at the ground level near hives. We also investigated how intraspecific competition can influence the feeding display in this species. Our results confirm the major role of the German yellowjacket as a scavenger, because its diet is based mostly on bee carrions. Intraspecific competition during feeding was sometimes observed. When these events occurred, the interference of another wasp led to the bee escaping only in three cases. Our study also revealed that intraspecific competition events increase when the resource is fresh (predation vs necrophagy), and that the number of competing wasps was significantly higher when the food consisted of pupae and drones, compared to adult bees. When competition involved two individuals (the most frequent case), the winner was frequently the first wasp to reach the resource in both predation and necrophagy events. This suggests that the energy invested in foraging or predating activity and in defence of prey is usually rewarded.